Company competitiveness and competitive advantages in tourism and hospitality - Cetinski, Vinka (Array, 2008)
Summary: Connection between competitive strategies and competitive advantages is described in details in this paper. Model of the research is located on the company level in tourism and hospitality. Applicative basis of the paper is founded on the Diamond of Competitiveness (Case Study) usage and is based on the qualitative research of small entrepreneurship in tourism and hospitality. The fact that every strategy is based on creating and sustaining competitive advantages implies that the principal task of company management is shaping company's competitive advantages. Management uses its knowledge, controls available resources and manages business processes and events of a company in tourism and hospitality